Strategic product creation : - Kerber, Ronald L. (McGraw-Hill, 2007)
Create and market the right product-fast Strategic Product Creationis a true working guide to developing market-savvy, cost-effective products and services. Delivering expert guidance in the five key stages of product development, authors Ronald Kerber and Timothy Laseter present real-world examples of industry leaders who have produced innovative products-giving you a foolproof blueprint for delivering customer satisfaction without breaking the bank. Provides not only practical experience, but a solid conceptual framework for developing your own product creation model Highlights seven principles of effective product creation Features instructive case studies of world-class leaders such as Walt Disney Imagineering, Whirlpool Corporation, Mars, Inc., and IBM Includes key questions and milestone decision issues from each stage of the product creation process Covers both short- and long-term strategies, coupled with suggestions for advanced technology Explains how to combine customer knowledge with external market needs to stimulate new product and service ideas Reveals ways to utilize your suppliers as a talent pool for process improvement and product innovation Addresses sensitive issues of branding and intellectual property rights.